Manipulating the constraints: hard debt, efficiency wages, and union rents - Wilson, L (University of Oxford, 2003)
Several papers have argued that firms can hide profits from unions with hard debt commitments. Alternatively, here we argue that unions can manipulate the non-shirking constraint and win higher efficiency wages. By creating a culture of mistrust and an opposition to supervision ex ante, unions can ensure higher wages ex post. This resistance to monitoring, nevertheless, leads to deadweight losses. In the absence of debt, it is shown that a sufficiently strong union will opt to minimise monitoring costs because the non-shirking constraint will no longer bind.